A Frequency Hybrid Multi-mode PWM Modulation Method for SiC Traction Inverter - HU Liang; FU Xiangyu; LYU Yongcan; FENG Ling; HU Dong (Kongzhi Yu Xinxi Jishu)
In order to improve the efficiency of the traction system, this paper researches the PWM control strategy of high-frequency SiC traction inverter system from multiple dimensions such as inverter switching frequency optimization, modulation strategy selection and motor control algorithm adaptation. A multi-mode PWM control method for SiC traction inverter is proposed in this paper. At low and medium speeds which below 30% rated speed, the high-frequency characteristics of SiC are fully utilized and the rated switching frequency of the inverter is optimized based on the principle of system loss optimization. During high speeds above 30% rated speed, the current harmonics are optimized modulated to achieve motor current harmonic suppression, while the motor voltage utilization rate can reach 97%. In addition, a new closed loop control method for multimodal stator flux trajectories of traction motors is proposed in order to adapt to the new PWM control method. The proposed PWM control method is compared with the traditional low-frequency PWM control method. Experimental results show that using the proposed algorithm, the total harmonic distortion (THD) of the motor current can be reduced by a maximum of 9.31%, the overall loss of the traction system can be reduced by a maximum of 10.2%, the temperature rise of the motor can be reduced by a maximum of 31 K, and the maximum noise suppression of the motor can reach 10 dB. Effectiveness of the proposed PWM modulation method is demonstrated.